The financial toxicity of breast cancer: a systematic mapping of the literature and identification of research challenges - Ratosa Ivica; Bavdaz Mojca; Bonca Petra Dosenovic; Logar Helena Barbara Zobec; Perhavec Andraz; Skubic Marjeta; Vörös Katja; Mihor Ana; Zadnik Vesna; Redek Tjasa (Radiology and Oncology)
Breast cancer is one of the most common cancers, increasingly prevalent also among working-age populations. Regardless of age, breast cancer has significant direct and indirect costs on the individuals, families and society. The aim of the research was to provide a comprehensive bibliometric analysis of the financial toxicity of breast cancer, to identify research voids and future research challenges.